How Should Public Administrations Foster the Ethical Development and Use of Artificial Intelligence? A Review of Proposals for Developing Governance of AI - Sigfrids, Anton; Nieminen, Mika; Leikas, Jaana; Pikkuaho, Pietari (Frontiers in Human Dynamics, 2022)
Recent advances in AI raise questions about its social impacts and implementation. In response, governments and public administrations seek to develop adequate governance frameworks to mitigate risks and maximize the potential of AI development and use. Such work largely deals with questions of how challenges and risks should be managed, which values and goals should be pursued, and through which institutional mechanisms and principles these goals could be achieved. In this paper, we conduct a systematic review of the existing literature on the development of AI governance for public administration. The article describes principles and means by which public administrations could guide and steer AI developers and users in adopting ethical and responsible practices. The reviewed literature indicates a need for public administrations to move away from top-down hierarchical governance principles and adopt forms of inclusive policy-making to ensure the actionability of ethical and responsibility principles in the successful governance of AI development and use. By combining the results, we propose a CIIA (Comprehensive, Inclusive, Institutionalized, and Actionable) framework that integrates the key aspects of the proposed development solutions into an ideal typical and comprehensive model for AI governance.